Identifikasi Alat Keselamatan Kerja Nelayan Kapal Purse Seine (Studi Kasus KM PIPOSS BERAU) yang Berpangkal di PPI Sambaliung - Ully Wulandari; M Natsir Kholis; Rini Sahni Putri; Syafiq Syafiq (Samakia : Jurnal Ilmu Perikanan, 2021)
The research was conducted in June-July 2020 at Sambaliung Fish Landing Base (PPI), Berau Regency, East Kalimantan Province. The purpose of this study was to identify safety equipment on purse seine ships at PPI Sambaliung. The method used is case study method by collecting data using observation method directly at KM Piposs Berau with systematic observation and recording of investigated phenomena and structured interviews. Analysis in this study was conducted using descriptive analysis of observation and interview results. The results of this study showed that the safety equipment on board KM Piposs Berau consists of 5 categories, namely: 1) Ship safety equipment: sea map, compass, GPS, radio, echosounder, bucket with rope, and strap to the ship, 2) Individual safety equipment: life jacket, life buoy, 3) Drug equipment (first aid), 4) Personal protective equipment: gloves, raincoats, 5) Work equipment: power blocks, rollers, joy stands, wheel, tools and workshop tools, as well as the thematic ropes.